Building Feedback Literacy: Students’ Perceptions of the Developing Engagement With Feedback Toolkit - Winstone, Naomi E.; Mathlin, Georgina; Nash, Robert A. (Frontiers in Education, 2019)
Developing the requisite skills for engaging proactively with feedback is crucial for academic success. This paper reports data concerning the perceived usefulness of the Developing Engagement with Feedback Toolkit (DEFT) in supporting the development of students’ feedback literacy skills. In Study 1, student participants were surveyed about their use of feedback, and their perceptions of the utility of the DEFT resources. In Study 2, students discussed the resources in focus groups. Study 3 compared students’ responses on a measure of feedback literacy before and after they completed a DEFT feedback workshop. Participants perceived the DEFT favourably, and the data indicate that such resources may enhance students’ general feedback literacy. However, the data raise questions about when such an intervention would be of greatest value to students, the extent to which students would or should engage voluntarily, and whether it would engage those students with the greatest need for developmental support.